2012
DOI: 10.1149/2.079302jes
|View full text |Cite
|
Sign up to set email alerts
|

Factors for Improvements of Catalytic Activity of Zirconium Oxide-Based Oxygen-Reduction Electrocatalysts

Abstract: Partially oxidized zirconium carbonitrides (Zr-CNO) were evaluated as a non-precious-metal cathode used for polymer electrolyte fuel cells. The zirconium-oxide-based catalysts were prepared from zirconium carbonitrides under controlled oxygen partial pressures from 10 −2 to 10 −18 atm at 1000 • C. The ORR activity of Zr-CNO showed a volcano-like tendency against the degree of oxidation (DOO). We found a significant lattice-parameter decrease for highly active Zr-CNOs, and this could be ascribed for the formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
40
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 46 publications
2
40
0
1
Order By: Relevance
“…15,16 The same group also applied surface sensitive X-Ray absorption spectroscopy, which suggested a correlation between ORR activity and defect-induced strain of the Ta 2 O 5 oxide layer formed on top of a μm-sized TaCN core upon high-temperature oxidation. 10 In order to increase the very low catalyst dispersion (i.e., the electrochemically active surface area per gram of catalyst) obtained with the above synthesis approaches, methods to synthesize highly dispersed Zr oxide nanoparticles supported on carbon black were investigated.…”
mentioning
confidence: 99%
“…15,16 The same group also applied surface sensitive X-Ray absorption spectroscopy, which suggested a correlation between ORR activity and defect-induced strain of the Ta 2 O 5 oxide layer formed on top of a μm-sized TaCN core upon high-temperature oxidation. 10 In order to increase the very low catalyst dispersion (i.e., the electrochemically active surface area per gram of catalyst) obtained with the above synthesis approaches, methods to synthesize highly dispersed Zr oxide nanoparticles supported on carbon black were investigated.…”
mentioning
confidence: 99%
“…We previously described the acidic stability and catalytic ORR activity of a number of materials, including tantalum-doped tungsten carbide, 15 tantalum oxynitride, [16][17][18] zirconium oxide, [19][20][21] titanium oxide, 22 zirconium oxynitride, 23,24 tantalum carbonitride, 25 and tantalum-oxide or zirconium-oxide-based compounds. [26][27][28] Recently, we revealed that zirconium oxide-based compounds prepared from oxy-zirconium phthalocyanine by heat treatment under low oxygen partial pressure showed high ORR activity. [28][29][30] These catalysts were composed of zirconium-oxide nano-particles supported by multi-walled carbon nanotubes (MWCNTs).…”
mentioning
confidence: 99%
“…[26][27][28] Recently, we revealed that zirconium oxide-based compounds prepared from oxy-zirconium phthalocyanine by heat treatment under low oxygen partial pressure showed high ORR activity. [28][29][30] These catalysts were composed of zirconium-oxide nano-particles supported by multi-walled carbon nanotubes (MWCNTs). We concluded that oxygen vacancies in the oxide particles acted as ORR active sites.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We focused on group 4 and 5 transition metal oxides, because they have high chemical stability under acidic atmosphere even in high potential region, and are much less expensive than platinum. In our previous study, zirconium oxide based compounds made from oxyzirconium phthalocyanines by heat treatment under low oxygen partial pressure showed high ORR activity (1)(2). Therefore, their durability and stabilization should be investigated.…”
Section: Introductionmentioning
confidence: 99%